THE EFFECT OF FREE CASH FLOWS TO THE RELATIONSHIP BETWEEN INVESTMENT RETURNS, DEVIDEND POLICY, AND STOCK RETURNS - ANIARTHA, P. D'YAN; WIDANAPUTRA, A.A.G.P. (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 2 No 1 (2007))
ABSTRAK
Keywords: FREE CASH FLOWS, RETURN ON INVESTMENT, KEBIJAKAN DEVIDEN, RETURN SAHAM